ANTIBIOTIC UTILIZATION PATTERN AT THE SURGERY DEPARTMENT OF A TERTIARY CARE HOSPITAL - Raut, Asawari; Cherian, Tirzah; Chauhan, Shreepa; Pawar, Atmaram (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study aims to determine the pattern of antibiotic utilization at the surgery department of a tertiary care hospital. Method: A prospective observational study was conducted over a period of 6 months period in surgical ward at Bharti Hospital and Research Centre, Pune, a 1000 bedded teaching hospital. Patients above 18 years and receiving antibiotic therapy pre and post-surgery were included in the study. Results:160 patients with surgical operations were included in the study.The disease spectrum was classified into respective system-wise surgical procedures of which 49.37% cases are skin & soft tissue infections, 25.62% cases of general surgical procedure, 12.5% cases of gastrointestinal surgical procedure, 11.25% cases of urinary system and 1.25% case of head neck system. 20.62% of the study patients had hernia, 18.12% patients had cellulitis, 16.87% patients had diabetic foot ulcer, 16.25% patients had abscess, and 10.62% patients had appendicitis and cholelithiasis. In this study, it was found that 471 antibiotics were used in total of 160 patients, among which highest group of antibiotics prescribed were third generation Cephalosporin (28.23%) followed by Penicillins (23.56%). The most frequently prescribed antibiotics were Metronidazole − 19.74% among the Nitroimidazoles followed by Ceftriaxone − 19.53% of the class Cephalosporins. Conclusion: The rate of prescribing of broad-spectrum antibiotics has increased demonstrably which may result in development of bacterial resistance; however development of guidelines for antibiotic prescription and use of appropriate drugs for the diseases can minimize the unfavourable use of antibiotics and cost of healthcare.